Implementation of Classroom Management to Foster Discipline Among Students in Grade V at SDN 2 Gledeg Klaten (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to determine the implementation, supporting factors, and impact of classroom management in grade V at SDN 2 Gledeg. Methodology: This study uses a qualitative approach, with teachers, students, and parents as participants. Data collection methods include interviews, observation, and documentation.Results: This research topic was chosen due to the importance of classroom management in shaping student discipline, which plays a major role in creating an orderly and conducive learning environment. The results of the study indicate that the implementation of classroom management at SDN 2 Gledeg through the POAC (Planning, Organizing, Actuating, and Controlling) approach is effective, with the support of student involvement, teacher role modeling, parent-school cooperation, a reward and punishment system, and effective communication between teachers, students, and parents. The impact is evident in increased awareness of discipline, a conducive classroom atmosphere, and higher student motivation to learn.Application, Originality, and Value: This study confirms the effectiveness of the POAC approach in classroom management and the importance of collaboration between teachers, students, and parents in establishing discipline and a conducive learning environment.